Effectiveness of TPACK types based on constructionist activities on students technological literation ability - Fauzatul Ma'rufah Rohmanurmeta; Herawati Susilo; Mohammad Zainuddin; Syamsul Hadi (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
This study aims to compare the effectiveness of the TPACK types which include TPACK-IK, TPACK-TK, TPACK-VK, and TPACK-V on students' technological literacy abilities. This type of research is pure experimental research. The research design used was pretest-posttest with nonequivalent groups. The population in this study amounted to 272 students. The sample of this study included 30 students in class A, 31 students in class B, 29 students in class C, and 30 students in class D. The data collection technique used in this study is the test. The research instrument used was the question sheet. The results showed that based on the results of the paired t test, it was found that there was a difference in the average pretest and posttest scores in the experimental group I with a P value of 0.001, the experimental group II with a P = 0.026, and control I with a P = 0.034. Whereas in the control group II there was no difference in the average pretest and posttest scores with P = 0.283. Based on these data the treatment with TPACK-IK gave the best results on students' technological literacy skills. Meanwhile, based on the Two Way Anova analysis, it shows that Fcount > Ftable with an acquisition score of 9.456 > 4.03 with P <0.05. The data shows that the four types of TPACK are able to differentiate students' technological literacy levels.